The Influence of The Problem Based Learning (PBL) Model on Motivation and Results in Fiqh Mawaris Learning at MAN 2 Sukabumi - Mu'min, U Abdullah; Khutomi, Budi Munawar; Nurjaman, Ujang (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2024)
The aim of this research is to determine: (1) the influence of the Problem Based Learning (PBL) model on the learning motivation of class XI Science students at MAN 2 Sukabumi and (2) the influence of the Problem Based Learning (PBL) model on the learning outcomes of class XI Science students at MAN 2 Sukabumi. This research uses a quasi-experimental research design using a pre-test and post-test group research design. The research results showed that there was no influence of PBL on the learning motivation of class XI Science students at MAN 2 Sukabumi. The influence of PBL on the learning outcomes of class XI Science students at MAN 2 Sukabumi in each domain is: (1) there is an influence of the PBL model on students' social attitude learning outcomes, (2) there is no influence of the PBL model on students' spiritual learning outcomes, (3) there is an influence of the PBL model on students' knowledge learning outcomes (4) there is an influence of the PBL model on learning outcomes student skills. The application of the PBL model to increase motivation so that it becomes optimal should be modified.